Playing with history : American identities and children's consumer culture - Rosner, Molly, 1986- (Rutgers University Press, 2021)
"Since the advent of the American toy industry, children's cultural products have attempted to teach and sell ideas of American identity. By examining cultural products geared towards teaching children American identity, Playing With History highlights the changes and constancies in depictions of the American story and ideals of citizenship over the last one hundred years. The book examines political and ideological messages sold to children throughout the twentieth century, tracing the messages conveyed by racist toy banks, early governmental interventions meant to protect the toy industry, infences and pressures surrounding Cold War stories of the western frontier, and the fractures visible in the American story at a mid-century history themed amusement park. This engaging analysis culminates in a look at the successes and limitations of the American Girl Company empire"--